Pemanfaatan Teknologi Pesawat Udara Tanpa Awak dalam Deteksi Pengedaran Narkoba di Selat Sunda - Putri, Cintya Yelena; Supriyadi, Asep Adang; Ras, Abdul Rivai (UNIB Press, 2025)
Drugs trafficking via Indonesia's sea routes continues to increase, making the Sunda Strait one of the most vulnerable points for inter-island smuggling. Conventional surveillance using patrol boats is often ineffective due to limitations in range, weather, and response time. This study was conducted to evaluate the potential and effectiveness of utilizing Unmanned Aerial Vehicle (UAV) technology in detecting and preventing drug trafficking in the Sunda Strait maritime region. The study used a qualitative approach through a Systematic Literature Review (SLR) that examined previous research results, national policies, and the implementation of UAVs in maritime security. The analysis was carried out by grouping the findings into four main themes, namely the effectiveness of UAVs in maritime surveillance, technical and operational constraints, integration with national security systems, and institutional policies and regulations. The results of the study show that UAVs can double the effectiveness of surveillance through real-time visual detection capabilities, wide coverage, and integration with radar and AIS systems. However, technical challenges such as battery life, extreme weather, and operator limitations still need to be overcome. The study concludes that the integrated application of UAVs, supported by strong institutional policies, can strengthen the national maritime security system and narrow the space for drug smuggling networks in the Sunda Strait.